Hubungan Pemakaian Alat Kontrasepsi Suntik Dengan Gangguan Menstruasi Pada Akseptor KB di RSUD. Dr. Tengku Mansyur Kota Tanjung Balai Tahun 2022 - Lambok Sitorus; Zulkarnain Batubara; Rosmega Rosmega (Pusat Riset dan Inovasi Nasional, 2024)
Menstrual cycle disorders are menstrual disorders, also known as abnormal uterine bleeding, which is a complaint that often causes women to seek treatment from a doctor or first aid center. There were 30 acceptors who experienced menstrual cycle disorders. The aim is to analyze the relationship between injectable contraceptive use and menstrual cycle disorders at Dr. Tengku Mansyur, Tanjung Balai city in 2022. The method used is an analytical survey, the research design used is cross sectional. The independent variable is injectable contraception. The dependent variable is menstrual cycle disorders in the population of all new acceptors of injectable contraception. Statistical tests use chi-square, research instruments use questionnaires. The results of the study were that most respondents used injectable contraception with menstrual cycle disorders as many as 30 (65.4%). The results of statistical tests using chis square showed p value = 0.000 with a significance level of α (0.05) and p < α (0.000 < 0.05), so H0 was rejected, which means there is a relationship between the use of injectable contraception and menstrual cycle disorders in family planning acceptors .Based on research results, efforts that can be made are by improving lifestyle, consuming healthy food and balancing activity patterns.